MOST IMPORTANT INVENTIONS AND FUTURE TECHNOLOGY IDEAS - Muxtarov Abduvali,; To`raxon Abdurahmonov, (TADQIQOTLAR, 2026)
Abstract Technological  development  has  played  a  crucial  role  in  shaping  human civilization  from  ancient  times  to  the  modern  digital  age.  Throughout  history, inventions have helped humanity overcome challenges, improve living standards, and expand knowledge. The rapid development of science and engineering in the last few centuries  has  resulted  in  groundbreaking  innovations  that  transformed  industries, economies,  and  societies.  Today,  the  pace  of  technological  progress  continues  to accelerate, creating new opportunities as well as challenges for humanity. This  thesis  explores  the  most  important  inventions  that  have  significantly influenced  human  development  and  examines  modern  technological  advancements that are shaping the present world. In addition, the research analyzes future technology ideas that scientists and engineers believe will transform society in the coming decades. By studying historical inventions and emerging technologies, we can better understand how innovation drives progress and how societies can adapt to technological change. Organizations such as MIT Technology Review and World Economic Forum continuously analyze technological trends and provide insights into the future of global innovation. Their research highlights the importance of investing in science, education, and research in order to create sustainable development and economic growth. This  thesis  aims  to  provide  a  comprehensive  understanding  of  technological evolution, its impact on society, and the potential direction of future innovations.